High Glamour Magical Clothing and Talismanic Fashion - Rodgers, Charlotte (2020)
The iconography and visuals associated with magic are highly evocative and responsible for a major part of its appeal. The strong, often iconoclastic imagery exerts a particularly powerful draw for the artist or craftsperson because of its ability to fire the imagination, and to inspire creative work in response. Until recent times, creative interpretations of magic within mainstream fashion have mainly been on a subtle and subversive level; generally within a counter cultural context. So why is magical symbolism being appropriated within high fashion at this particular point in time?
Keywords: Contemporary Paganism; Tarot; Aesthetics; couture; Fashion